Equatorial Undercurrent in the central Atlantic and its relation to tropical Atlantic variability - Brandt, Peter; Funk, Andreas; Tantet, Alexis; Johns, William E; Fischer, Jürgen (Climate dynamics, 2014)
Seasonal to interannual variations of the Equatorial Undercurrent (EUC) in the central Atlantic at 23°W are studied using shipboard observation taken during the period 1999–2011 as well as moored velocity time series covering the period May 2005–June 2011. The seasonal variations are dominated by an annual harmonic of the EUC transport and the EUC core depth (both at maximum during September), and a semiannual harmonic of the EUC core velocity (maximum during April and September). Substantial interannual variability during the period of moored observation included anomalous cold/warm equatorial Atlantic cold tongue events during 2005/2008. The easterly winds in the western equatorial Atlantic during boreal spring that represent the preconditioning of cold/warm events were strong/weak during 2005/2008 and associated with strong/weak boreal summer EUC transport. The anomalous year 2009 was instead associated with weak preconditioning and smallest EUC transport on record from January to July, but during August coldest SST anomalies in the eastern equatorial Atlantic were observed. The interannual variations of the EUC are discussed with respect to recently described variability of the tropical Atlantic Ocean.